Pengaruh Risiko, Materialitas, Internal Control Relevan Audit, Kompleksitas Audit Terhadap Pertimbangan Auditor Atas Prosedur Audit - Agustine Sulviani (Jurnal Wacana Ekonomi, 2019)
Considering exact audit approach, planning and perform advance audit procedure based on risk assessment which identified whether it’s financial statement or assertion level, These were auditor professional judgment, recognizing the highest amount of materiality misstatements which influence the user of financial statement in their decision. If classess of transactions consisted low inherent risk, only the substantive analytical procedures necessary would be provide audit evidence sufficiently. However, if risks assessed are low because of the participation of internal control relevance to audit, then the auditor will test the internal control as well. Initially, process and bookkeeping complex transactions are motivated auditor to perform audit procedure and relevant activity to obtain relevant information. Their motivation is because they believe in every transactions contained risk factors due to fraud or error and its occured beyond their insights. The aim of this study is to recognize whether audit risk, materiality, internal control relevance to audit and audit complexity are related with the auditor profesional judgment in audit procedure. The study carried out on public accountants whose registered in BPK-RI and they  served on audit firm in Bandung. The study using non probability techniques to select the sample, as of 29 selected public accountants have gathered as respondents. Analyzed data statistics examined the hypothesis using t and f tests showed that the audit risk, materiality, internal control relevance to audit and audit complexity have significance effects on profesional judgment in audit procedures, whether it is individual or together.